2016
DOI: 10.1002/ece3.2189
|View full text |Cite
|
Sign up to set email alerts
|

Mate choice for neutral and MHC genetic characteristics in Alpine marmots: different targets in different contexts?

Abstract: Sexual selection through female mate choice for genetic characteristics has been suggested to be an important evolutionary force maintaining genetic variation in animal populations. However, the genetic targets of female mate choice are not clearly identified and whether female mate choice is based on neutral genetic characteristics or on particular functional loci remains an open question. Here, we investigated the genetic targets of female mate choice in Alpine marmots (Marmota marmota), a socially monogamou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 104 publications
0
20
2
Order By: Relevance
“…Additionally, the length of the studies and of the pair-bonds differ greatly among species in the data set. Although some studies provided data from multiple breeding seasons or years (e.g., Alpine marmots, Ferrandiz-Rovira et al, 2016), others either did not follow pairs across multiple seasons or only sampled within one breeding season (e.g., Bornean gibbon, Oka and Takenaka, 2001). Finally, although our three indices of genetic monogamy are each different ways to quantify genetic monogamy, they are not necessarily of equal biological importance.…”
Section: Summary Of Main Findingsmentioning
confidence: 97%
“…Additionally, the length of the studies and of the pair-bonds differ greatly among species in the data set. Although some studies provided data from multiple breeding seasons or years (e.g., Alpine marmots, Ferrandiz-Rovira et al, 2016), others either did not follow pairs across multiple seasons or only sampled within one breeding season (e.g., Bornean gibbon, Oka and Takenaka, 2001). Finally, although our three indices of genetic monogamy are each different ways to quantify genetic monogamy, they are not necessarily of equal biological importance.…”
Section: Summary Of Main Findingsmentioning
confidence: 97%
“…Extra‐pair behaviours are also associated with genetic characteristics, especially the relatedness of the dominant pair measured with microsatellites. Higher EPP levels are observed for both low and high within‐pair relatedness, whereas lower EPP levels are observed at intermediate within‐pair relatedness (Cohas et al ., ; Ferrandiz‐Rovira et al ., ).…”
Section: Methodsmentioning
confidence: 97%
“…In this socially monogamous species, social pair‐bonding lasts until the death or eviction of one member of the dominant pair by a third individual and divorce is never observed (Lardy et al ., ). Dominant males never reproduce with any female other than the dominant female, but a strategy for a female to counteract a suboptimal social mate choice is to obtain extra‐pair paternities (EPPs) (Cohas et al ., ; Ferrandiz‐Rovira et al ., ). Marmots live in families, and the social context is an extrinsic factor strongly constraining the proportion of extra‐pair young (EPY) (Cohas et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…The annual number of recruits per individual ( NR ti ) was estimated as the number of offspring produced per individual (determined by genetic kinship analyses) that survived the first hibernation. More details on the study species, the study area, and the genetic analyses can be found elsewhere (Allainé & Theuriau, ; Cohas, Yoccoz, & Allainé, ; Ferrandiz‐Rovira, Allainé, Callait‐Cardinal, & Cohas, ).…”
Section: Methodsmentioning
confidence: 99%
“…Balanced α π = 0 (π = 0.5) , 2004;Cohas, Yoccoz, & Allainé, 2007;Ferrandiz-Rovira, Allainé, Callait-Cardinal, & Cohas, 2016).…”
Section: Proportion Of Individuals In Each Clustermentioning
confidence: 99%